Artificial neural network model for the prediction of the "El Niño" phenomenon in the region of Piura (Peru) - Peña Cáceres, Oscar J. M.; More More, Manuel A.; Espinoza Nima, Rudy; Silva Marchan, Henry (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
El Phenomenon El Niño is an event of climatic origin. In 2017 this event will impact the region Piura, Peru. The heavy rainfall generated the overflow of the Piura River that affects the districts of Piura, Castilla, Catacaos and Cura Mori. The objective of the study is to identify the most influential variables and to have a model that predicts the occurrence of the El Niño Phenomenon in the Piura region, through the use of Artificial Neuronal Networks. The results indicate that the Surface Temperature of the Sea is the most influential variable. The model has an accuracy of 82% accuracy.